International carriage of goods by road : CMR - Clarke, Malcolm A. (Malcolm Alistair) (Milton Park, Abingdon, Oxon : Informa Law from Routledge, 2014)
'Now in its sixth edition, this key text provides a comprehensive analysis of the international carriage of goods by road under the provisions of the CMR Convention. The author offers unparalleled coverage of both English and European case law in a text that is praised for its accessible, user-friendly style.This new edition is fully updated with the very latest in case law and legislation both internationally and on a domestic level, including:New developments on the applicability of the CMR to multimodal transport, as per the Godafoss caseThe concept of the'wilful misconduct' in the light of the German Transport Law Reform Act 1998 and the new Dutch Civil CodeThorough analysis of TNT Express Nederland BV v AXA Versicherung AGIt also provides new coverage of the impact of e-commerce on road haulage.This book is an invaluable reference tool for transport practitioners with an international and domestic client base. It is also a useful guide for academics and students of the carriage of goods by road'--
Part I: The CMR -- Application of the CMR -- The contract of carriage : documentation -- The journey -- Claims -- The liability of the carrier -- Defences available to the carrier -- The special risks -- Remedies -- Part II: English domestic law -- The contract of carriage -- The journey -- Claims -- The liability of the carrier -- Defences -- Remedies.
Includes bibliographical references and index.
Keywords: Convention on the Contract for the International Carriage of Goods by Road -- (1956); Trucking -- Law and legislation -- England; Transportation, Automotive -- Law and legislation -- England; International and municipal law -- United Kingdom; Trucking -- Law and legislation -- Europe; Transportation, Automotive -- Law and legislation -- Europe